2023
DOI: 10.1098/rspb.2023.1185
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown in seasonal dynamics of subtropical ant communities with land-cover change

Jamie M. Kass,
Masashi Yoshimura,
Masako Ogasawara
et al.

Abstract: Concerns about widespread human-induced declines in insect populations are mounting, yet little is known about how land-use change modifies both the trends and variability of insect communities, particularly in understudied regions. Here, we examine how the seasonal activity patterns of ants—key drivers of terrestrial ecosystem functioning—vary with anthropogenic land-cover change on a subtropical island landscape, and whether differences in temperature or species composition can explain observed patterns. Usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…As expected, community composition of male ants flying during the wet and dry seasons were significantly different. Seasonal effects on ant communities are widespread for tropical ant communities [48][49], especially in seasonally dry forests [11], varying both in temperature and precipitation regimes [50]. Nonetheless, in this long-term study (16 years), only a small directional trend was observed for community composition, and this occurred only for the wet season assemblages.…”
Section: Discussionmentioning
confidence: 60%
“…As expected, community composition of male ants flying during the wet and dry seasons were significantly different. Seasonal effects on ant communities are widespread for tropical ant communities [48][49], especially in seasonally dry forests [11], varying both in temperature and precipitation regimes [50]. Nonetheless, in this long-term study (16 years), only a small directional trend was observed for community composition, and this occurred only for the wet season assemblages.…”
Section: Discussionmentioning
confidence: 60%
“…The data that support the findings of this study and all R code to reproduce the analyses are available in the Zenodo digital repository as Ross, S. R. P.-J., Friedman, N. R., Dudley, K. L., Yoshimura, M., Yoshida, T., Economo, E. P., Armitage, D. W., & Donohue, I. (2023).…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 67%
“…For example, our focal species differ in their seasonality and phenology, meaning that natural phenological differences may be in part responsible for the differences in species' typhoon responses we observed here. A recent study of Okinawan ants showed that ant activity was more seasonal in forested than developed field sites, and that these patterns in seasonality were driven by asynchronous seasonal dynamics of different ant species at the community level (Kass et al., 2023). This raises the possibility that land development degraded seasonal dynamics in the soundscape, possibly contributing to differences in the spatial divergence of SPL High among forested but less so among developed field sites.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our focal species differ in their seasonality and phenology, meaning that natural phenological differences may be in part responsible for the differences in species’ typhoon responses we observed here. A recent study of Okinawan ants showed that ant activity was more seasonal in forested than developed field sites, and that these patterns in seasonality were driven by asynchronous seasonal dynamics of different ant species at the community level (Kass et al, 2023). This raises the possibility that land development degraded seasonal dynamics in the soundscape, possibly contributing to differences in the spatial divergence of SPL High among forested but less so among developed field sites.…”
Section: Discussionmentioning
confidence: 99%